THE POSITION OF VICE MINISTER AND THE IMPLICATION THEREOF ON INDONESIA’S CONSTITUTIONAL LAW - Rusnan SH (Jurnal IUS Kajian Hukum dan Keadilan, 2013)
According to article 17 (2) of the Constitution of Republic of Indonesia: “ministries are appointed and dismissed by President”, the appointment of a minister is president’s authority. Based on this article, the appointment of a vice ministry then will be a part of president’s authority as well. Hence, it is necessary to stress that the appointment of vise minister is not contrary to the constitution. In relation with the legal stand of vise minister, article explanation 10 of Law No 30 of 2008 stipulates: “vise minister is career official and not cabinet member”. In its decision, constitutional court considers that such article explanation is not conformed to the article 9 (1) of Law No 30 of 2008, because the latest article explains that the ministerial structure consists of:  minister, leading assistance i.e., general secretary, the primary task executor, i.e. general directory, inspector, i.e. general inspektorat, back-up task i.e. central and local agent as well as the primary task executor at local level and, or, abroad by deputy in accordance with the regulations. If the vise minister appointed as a career official then he/she no longer has any position, and that’s not conformed to the ministerial structure, that is also incompatible with article 9 of Law No 39 of 2008. This fact brings about the legal uncertainty and it’s contradicted to article 28D (1) of the Constitution of Republic of Indonesia.  According to constitutional court decision No. 79/PUU-IX/2011, its fulfills a part of the pleader’s request on judicial review to article 10 Law No 39 of 2008 on state ministries by nullifying the explanation of the such article because it contrasts to the constitution and hasn’t any legal force. In its decision, constitution court also instructs president to amend the old presidential decision in order that it’s conformed to executive authority and does not bring about legal uncertainty.Keywords: The Vice Minister’s , Legal Standing, Constitutional Court Decision